Interaction of Salmonella enterica serovar Typhi with cultured epithelial cells: roles of surface structures in adhesion and invasion. - Bishop, A; House, D; Perkins, T; Baker, S; Kingsley, R; Dougan, G (2008)
In this study we investigate the ability of Salmonella enterica serovar Typhi (S. Typhi) surface structures to influence invasion and adhesion in epithelial cell assay systems. In general, S. Typhi was found to be less adherent, invasive and cytotoxic than S. enterica serovar Typhimurium (S. Typhimurium). Culture conditions had little effect on adhesion of S. Typhi to cultured cells but had a marked influence on invasion. In contrast, bacterial growth conditions did not influence S. Typhi apical invasion of polarized cells. The levels of S. Typhi, but not S. Typhimurium, invasion were increased by application of bacteria to the basolateral surface of polarized cells. Expression of virulence (Vi) capsule by S. Typhi resulted in a modest reduction in adhesion, but profoundly reduced levels of invasion of non-polarized cells. However, Vi capsule expression had no affect on invasion of the apical or basolateral surfaces of polarized cells. Mutation of the staA, tcfA or pilS genes did not affect invasion or adhesion in either the presence or the absence of Vi capsule.